High-resolution fluence verification for treatment plan specific QA in ion beam radiotherapy - Martišíková, Mária; Brons, Stephan; Hesse, Bernd; Jäkel, Oliver (Physics in medicine and biology, 2013)
Ion beam radiotherapy exploits the finite range of ion beams and the increased dose deposition of ions toward the end of their range in material. This results in high dose conformation to the target region, which can be further increased using scanning ion beams. The standard method for patient-plan verification in ion beam therapy is ionization chamber dosimetry. The spatial resolution of this method is given by the distance between the chambers (typically 1 cm). However, steep dose gradients created by scanning ion beams call for more information and improved spatial resolution. Here we propose a clinically applicable method, supplementary to standard patient-plan verification. It is based on ion fluence measurements in the entrance region with high spatial resolution in the plane perpendicular to the beam, separately for each energy slice. In this paper the usability of the RID256 L amorphous silicon flat-panel detector for the measurements proposed is demonstrated for carbon ion beams. The detector provides sufficient spatial resolution for this kind of measurement (pixel pitch 0.8 mm). The experiments were performed at the Heidelberg Ion-Beam Therapy Center in Germany. This facility is equipped with a synchrotron capable of accelerating ions from protons up to oxygen to energies between 48 and 430 MeV u−1. Beam application is based on beam scanning technology. The measured signal corresponding to single energy slices was translated to ion fluence on a pixel-by-pixel basis, using calibration, which is dependent on energy and ion type. To quantify the agreement of the fluence distributions measured with those planned, a gamma-index criterion was used. In the patient field investigated excellent agreement was found between the two distributions. At least 95% of the slices contained more than 96% of points agreeing with our criteria. Due to the high spatial resolution, this method is especially valuable for measurements of strongly inhomogeneous fluence distributions like those in intensity-modulated treatment plans or plans including dose painting. Since no water phantom is needed to perform measurements, the flat-panel detector investigated has high potential for use with gantries. Before the method can be used in the clinical routine, it has to be sufficiently tested for each detector-facility combination.